Drug Interaction of Hypericum Perforatum with Routine Chemical Drugs - Reza Assadzadeh; Shabnam Shamaei; Aliasghar Manouchehri (Institute of Medico-legal Publications Pvt Ltd, 2021)
In traditional medicine, Hypericum perforatum L. is used as an antidepressant, diuretic, analgesic, antisepticand wound healing, anticonvulsant, rheumatism and chronic gastrointestinal spasms, abortion, sciatica, andfor the treatment of infectious diseases such as syphilis, tuberculosis, dysentery, pertussis, worm excretion,and malaria. H. perforatum interferes with cardiac drugs, anesthetics, narcotics and analgesics, antibiotics,hormonal compounds, antiviral compounds, anticonvulsants and antidepressants, organ transplantationcompounds, and iron compounds. Despite the medicinal effects of the valuable plant H. perforatum, thesingle use of this plant is very effective and valuable in the treatment of diseases and disorders, but its usewith other chemical drugs due to the occurrence of drug interactions requires caution in consumption.